Negotiating Child-Friendly Education in Islamic Early Childhood Settings: A Moral-Relational Pedagogy - Abdulhamid Al-Khateeb, Mohammed; 'Aziz, Hafidh (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study examines how teachers in Islamic early childhood education settings understand child-friendly education, how they translate it into everyday classroom practice, and how its enactment is negotiated under social and institutional constraints. It addresses a gap in existing scholarship, which has tended to privilege policy frameworks, institutional indicators, and moral discourse over the pedagogical work through which child-friendly education is interpreted and sustained in daily educational relations.Design/methods/approach – The study employed a descriptive exploratory qualitative design. Data were generated through semi-structured interviews and non-participant observations involving eight teachers across eight anonymised Islamic early childhood education settings in the Special Region of Yogyakarta, Indonesia. The data were analysed using qualitative content analysis, guided by an interpretive framework that brought into dialogue Islamic pedagogy, a rights-based perspective on child-friendly education, and an ecological understanding of contextual constraint.Findings – The findings show that child-friendly education in Islamic early childhood education settings is not best understood as a technical framework, a completed institutional condition, or a self-evident extension of religious morality. Rather, it takes shape as a negotiated moral-relational pedagogy in which protection, participation, emotional safety, dignity, and moral-religious habituation are continuously mediated through teacher judgment and everyday classroom interaction. These commitments become visible in value-based practices, including respectful communication, non-dominating guidance, participation, inclusion, and safe routines. However, their enactment remains uneven because it is shaped by parental expectations, uneven pedagogical understanding among educators, children’s differing characteristics, and institutional limitations.Research implications/limitations – The study reframes child-friendly Islamic early childhood education as a negotiated moral-relational pedagogy rather than formal compliance, while its small, teacher-centred, region-specific sample limits the findings to interpretive depth rather than statistical generalisation.Practical implications – Strengthening child-friendly Islamic early childhood education requires teacher professional development, parent-school engagement, and institutional support to navigate tensions among care, authority, participation, discipline, and moral formation consistently.Originality/value – This article contributes to wider Muslim societies and global debates by showing that children’s rights and Islamic moral-religious education are neither inherently harmonious nor contradictory, but must be pedagogically integrated and continually negotiated through everyday practices of dignity, participation, protection, and moral formation in faith-based early childhood education.Paper type Research paper